Comparación de las pruebas de inmunofluorescencia indirecta, fijación del complemento y aglutinación en tarjeta para el diagnóstico de la anaplasmosis bovina. (1978)
Indirect fluorescent antibody test (IFA), complement fixation test (CF) and card agglutination test (CT) were statistically compared in 380 serum samples obtained from free animals and experimentally infected with Anaplasma marginale. It was found that IFA test was most sensitive for detection of animals infected with anaplasmosis (961k), followed by the CT test (84%) and the CF test (79%). The most specific test was the CF test (100%), followed by the CT test (98%) and the IFA test (90%). Significant differences were found when the IFA sensitivity was compared with the CF and CT sensitivities and when the specificities of IFA and CF tests were compared. A linear regression analysis performed on the average IFA and CF titers of 10 artifitially infected calves with A. marginale during a 20 week period, showed significant regression coeficients for both tests. The regression line for the CF titers decreased below the sensititvity threshold at 14 weeks FL, while the regression line for the IFA titers was still above the sensitivity threshold 20 weeks P1, the last period tested. The card test was still detecting antibodies at the end of the observation period. The results of this work indicated that IFA and CF test are valuable tests in prevalence studies when it is important to detect cronic carriers of anaplasmosis. Because of their high specificity the CF and CT test would be more valuable in anaplasmosis control or eradication programs.